Does Socioeconomic Status Influence Achievement? An analysis of the Performance of Kosovar Students on the 2015 and 2018 PISA Assessment - Shala, Arif; Grajcevci, Albulene; Latifi, Fadil (Revija za elementarno izobraževanje, 2021)
Socioeconomic status has long been considered aninfluential factor in student achievement. Similar to existing literature, resultsof this analysis reveal that socioeconomic status influenced studentachievement in the 2015 and 2018 PISA assessments. However, theachievement gap between categories widened between 2015 and 2018.Results reveal that home possessions, school location, parental educationplayed a role in achievement. Furthermore, students who attended privateschools outperformed students in public schools, a gap that widenedconsiderably between assessments. Results of the current analysis reveal theimportance of socioeconomic factors in achievement and, the need forpolicy builders to mitigate this impact.
Keywords: Socioeconomic status, Student achievement PISA, Kosovo